2018
DOI: 10.1016/j.mex.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of friction stir welding using machine learning approaches

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Gaussian process regression (GPR) is based on assumption that there is a directional likelihood between input and output for any model of the process. When the input is (x) and output is (y), the conditional distribution of the probabilities become p (y/x) [116]. The regression process by using Gaussian distribution is built on a collection of random values and that every point provided in the model delivers information of the adjacent value afterwards [86,117].…”
Section: Gaussian Process Regressionmentioning
confidence: 99%
“…Gaussian process regression (GPR) is based on assumption that there is a directional likelihood between input and output for any model of the process. When the input is (x) and output is (y), the conditional distribution of the probabilities become p (y/x) [116]. The regression process by using Gaussian distribution is built on a collection of random values and that every point provided in the model delivers information of the adjacent value afterwards [86,117].…”
Section: Gaussian Process Regressionmentioning
confidence: 99%
“…Verma et al [10] used various machine learning approaches like Gaussian Process Regression (GPR), Support Vectors Machine (SVM), and Multi Linear Regression (MLR) for performance evaluation in Friction Stir Welding process. It was observed that in comparison to SVM and MLR techniques, GPR approach works better for prediction of the Ultimate Tensile Strength (UTS) of the welded joints.…”
Section: Application Of Machine Learning In Friction Stir Welding Promentioning
confidence: 99%
“…Verma et al [9] used various sophisticated machine learning approaches like . Support Vector Machining (SVM) , Gaussian Process (GP) regression, and multi-linear regression (MLR) for evaluating the friction stir welding process.…”
Section: Application Of Machine Learning In Friction Stir Welding Promentioning
confidence: 99%